Ileo-anal pouch excision and permanent ileostomy – Indications and outcomes from a tertiary centre. Issue 4 (August 2020) - Kalaiselvan, R.; McWhirter, D.; Martin, K.; Byrne, C.; Rooney, P.S.
Abstract: Purpose: Pouch excision is a major complication of ileoanal pouch surgery. Current practice is for this type of surgery to be performed in a specialist centre. We present a series of patients undergoing pouch excision surgery in a high volume centre in the UK and assess the outcomes in these patients. Methods: All patients undergoing pouch excision at the Royal Liverpool Hospital between 1995 and 2015 under the care of a single surgeon were included. Demographics and outcomes were taken from patients' notes and a dedicated retrospectively compiled database. Results: 35 patients underwent pouch excision surgery during this period. Around half the patients had their original pouch surgery elsewhere and were referred for management of complications. Median time to pouch excision was 13 years from the original operation. Overall complication rate was 31% with 11% requiring re-intervention post-operatively. There was no mortality in this series. Conclusion: Pouch excision is a complex, high-risk procedure that should be carried out in specialist centres. Our series shows that in such settings, good outcomes can be achieved for these patients. Highlights: Ileoanal pouch excision is a rare but devastating complication of pouch surgery. The procedure is associated with significant morbidity for patients. Low numbers make experience in this type of surgery essential. Good outcomes cane be achieved by specialist units.